2023
DOI: 10.1021/acs.analchem.3c02658
|View full text |Cite
|
Sign up to set email alerts
|

Revolutions in Lipid Isomer Resolution: Application of Ultrahigh-Resolution Ion Mobility to Reveal Lipid Diversity

Berwyck L.J. Poad,
Lachlan J. Jekimovs,
Reuben S.E. Young
et al.

Abstract: Many families of lipid isomers remain unresolved by contemporary liquid chromatography−mass spectrometry approaches, leading to a significant underestimation of the structural diversity within the lipidome. While ion mobility coupled to mass spectrometry has provided an additional dimension of lipid isomer resolution, some isomers require a resolving power beyond the capabilities of conventional platforms. Here, we present the application of high-resolution traveling-wave ion mobility for the separation of lip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Especially in the case of TWIM-MS lipidomics applications, it has been shown that either a calibration , or an external postcalibration correction using (class-specific) lipids leads to an improved trueness of CCS values compared to DT CCS and/or published TW CCS values. Moreover, high-resolution IM analyzers, including structures for lossless ion manipulation (SLIM) and cyclic IMS offer new possibilities for challenging lipid isomer separations for which a CCS calibration provides new challenges. Recent studies revealed that TIM CCS values of lipids generally show good agreement with DT CCS when relying on external calibration using the same calibrant ions (ESI Tune Mix calibration standard). , However, a CCS recalibration of each analytical run is recommended in this type of workflow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in the case of TWIM-MS lipidomics applications, it has been shown that either a calibration , or an external postcalibration correction using (class-specific) lipids leads to an improved trueness of CCS values compared to DT CCS and/or published TW CCS values. Moreover, high-resolution IM analyzers, including structures for lossless ion manipulation (SLIM) and cyclic IMS offer new possibilities for challenging lipid isomer separations for which a CCS calibration provides new challenges. Recent studies revealed that TIM CCS values of lipids generally show good agreement with DT CCS when relying on external calibration using the same calibrant ions (ESI Tune Mix calibration standard). , However, a CCS recalibration of each analytical run is recommended in this type of workflow.…”
Section: Introductionmentioning
confidence: 99%
“…■ EXPERIMENTAL SECTION Sample Preparation. As samples, an unlabeled and a uniformly 13 C-labeled ethanolic yeast (Komagataella phaff ii) extract pellet 16 were provided by Isotopic Solutions (Vienna, Austria). The yeast extract pellets were re-extracted using a two-phase lipidomics extraction based on methyl tert-butyl ether (MTBE) modified from Matyash et al 26 More details on the extraction procedure can be found in the Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%